Trans‐rectovesical pouch urethral‐sparing robotic‐assisted simple prostatectomy: A case series - Xinnan Chen; Kangkang Zhao; Hao Wang; Chengwei Zhang; Lin Du; Wendi Wang; Tianyi Chen; Haixiang Qin; Xuefeng Qiu; Hongqian Guo; Gutian Zhang (BJUI Compass)
Abstract Objective To detail a novel technique of robotic‐assisted simple prostatectomy that makes handling the gland protruding into the bladder neck easier and can preserve the urethra and retain ejaculation function as much as possible. Patients and methods This is a prospective case series. Clinical data of 17 male patients who had large volume (>80 mL) benign prostatic hyperplasia (BPH) were enrolled to undergo trans‐rectovesical pouch urethral‐sparing robotic‐assisted simple prostatectomy (usRASP). We adopted the approach through the space between the bladder neck and seminal vesicle to perform a usRASP that can avoid the detrusor skirt and fibrous matrix area of the retropubic prostate. Between the transitional zone and the peripheral zone of the large prostate, the hyperplastic prostatic gland tissue can be enucleated under direct vision while preserving the prostatic urethra and retaining the ejaculatory duct and bladder neck intact. All preoperative, perioperative and postoperative clinical data were collected, and descriptive analysis was performed. Results The median intravesical prostatic protrusion was 19.3 mm (8.5–32.2). The median operative time was 100 min (75–140), and the median estimated blood loss was 100 mL (10–500). The median time to catheter removal was 7 days (5–7), with a median postoperative hospital stay of 2 days (2–4). After at least 6‐month follow‐up, the median maximum urine flow rate and postvoid residual volume were 40.1 mL/s (12.7–52.4) and 15 mL (5–23), respectively; the median International Prostate Symptom Score and Quality of Life score were 0 (0–6.3) and 1 (0–3), respectively; and the median total prostate‐specific antigen was 0.84 ng/mL (0.15–1.01). All patients successfully underwent usRASP. Fifty‐eight percent of patients with normal ejaculation function before surgery can still retain normal ejaculation function. Conclusion We described a new approach to performing usRASP. This new method remarkably improved the voiding function, maintained antegrade ejaculation and did not increase the post‐operative complications.